Effect of Nitrogen Addition on the ?-Amylase Production by Aspergillus niger, Rhizopus oligosporus and Neurospora crassa in media contained Sargassum and Rice Seed on Solid State Fermentation - Kanti, Atit (JURNAL BIOLOGI INDONESIA, 2016)
ABSTRACTAmylase is one of the hydrolytic enzymes which is commercially important and represent about 25â33% of the world enzyme market. Amylase production is affected by substrate for enzyme productions include particle size, initial moisture content and nutrient addition. The present study describe the effect of N-species addition on alpha amylase production by Aspergillus niger Km1, Rhizopus oligosporus Km2 and Neurospora crassa Km3 in medium contained sargasum and rice seed on solid state fermentation. Various ration of media composition contained dried sargassum and rice seed were studied. The effect of particle size of sargassum, initial water content on ?-amylase production were evaluated. The best media composition was then augmented with N-species include sodium nitrate, yeast extract, and peptone on solid state fermentation. Best media composition was 60:40 (w/w) of sargassum and rice seed respectively, with initial moisture content was 60%. Increase 5 times of amylase activity was obtained when sodium nitrate (0,5% w/w) was added to production medium. N-species significantly affect Alpha amylase production on sargassum and rice seed with maximum alpha amylase production was 36,66 unit by Rhizopus oligosporus.The economic value of Sargassum can be increased through alpha amilase production.Keywords: Amylase, Nitrogen, solid state fermentation, Rhizopus oligosporus, Neurospora crassa